Investigating phytochemical diversity and antioxidant richness of Moringa oleifera in Tamil Nadu - Dahiya, Sanju; Garg, Munish (Creative Pharma Assent, 2024)
Background: Moringa oleifera Lam., widely known as ‘The Tree of Life’, is a medicinal tree native to India and extensively grown in tropical regions worldwide. In India, Tamil Nadu is the leading state, engaging an area of 20684 hectares in the production of moringa. In South India, moringa is extensively utilized as a vegetable for its exquisite taste and flavor in sambar and curry preparation. Methodology: Phytochemical analysis of leaves from the Tamil Nadu region and simultaneous estimation of quercetin, rutin, and gallic acid contents in moringa leaf extracts from the Tamil Nadu region via HPTLC analysis was carried out. DPPH assay was performed to determine the antioxidant potential. Results and Discussion: The hydroalcoholic extract obtained from the triple maceration of moringa leaves possesses high amounts of phytoconstituents such as flavonoids and polyphenols. Each gram of the extract contained 1650.401 µg of quercetin, 1136.950 µg of rutin, and 220.223 µg of gallic acid. The IC50 value of the extract was calculated to be 36.10 µg/ml. Conclusion: The extract from the leaves of the moringa plant grown in the Tamil Nadu region contains a good amount of phytoconstituents and also possesses good antioxidant activity comparable to that of standard ascorbic acid, suggesting its potential use as an antioxidant agent. The findings of the present study support the traditional use of the folklore plant for improving health.